Flexible Ion-Gated Transistors Making Use of Poly-3-hexylthiophene (P3HT): Effect of the Molecular Weight on the Effectiveness of Gating and Device Performance - Lan, Tian; Gao, Zhaojing; Barbosa, Martin S. [UNESP]; Santato, Clara (Springer, 2020)
Poly-3-hexylthiophene (P3HT) is a benchmark semiconducting polymer in organic electronics. Ion-gated transistors (IGTs), making use of ionic gating media, are particularly interesting for flexible and printable& x2423;organic electronic applications. The molecular weight of P3HT is known to affect the morphology and structure of the corresponding films and, ultimately, the performance of devices based thereon. Here we report on IGTs based on films of P3HT with different molecular weights (similar to 20 kDa, 30-50 kDa and 80-90 kDa) and, as the gating medium, the well-investigated ionic liquid [EMIM][TFSI], to investigate the effects of the film morphological and structural properties on charge carrier transport and, eventually, IGT performance. P3HT films were deposited over rigid (SiO2/Si) and flexible (polyimide) substrates. All the P3HT IGTs could be operated at low voltage (about 1 V) and achieved a hole mobility larger than 0.1 cm(2) V-1 s(-1), pointing to the extremely favorable [EMIM][TFSI]/P3HT interface for IGT applications, for all the molecular weights investigated. We finally investigated the stability of flexible devices considering two different bending radii (R = 10 mm andR = 5 mm).
Keywords: Poly-3-hexylthiophene (P3HT); bendable polymer substrates; ion-gated transistors; ionic liquids